Page 2 of 3 FirstFirst 123 LastLast
Results 11 to 20 of 25

Thread: Is this correct

  1. #11
    New Member
    Join Date
    Jul 2005
    Location
    Vermont
    Posts
    12

    are these correct

    (x-y)(y-x) if x=-2 y=3
    (-2-3)(3-2)
    (-5)(1)=-5
    ----------------------
    (x-y)-(x-y) if x=-2 y=3
    (-2-3)-(-2-3)
    -5+5=0
    ------------------------
    (-x)+(-y) if x=-2 y=3
    (-2)+(-3)=5
    ----------------------
    -xa(x-a) if a =-2 x=4
    -4(-2)(-2-4)
    8*6=48
    and thanks for the help I appreciate it
    Benita

  2. #12
    Senior Member
    Join Date
    Jul 2005
    Location
    Christchurch, New Zealand
    Posts
    1,136
    G'day, Benita!

    If I number each...

    1) Be careful, you made the same mistake as I mentioned before.

    2) Good (you can go straight to zero in the future: a - a = 0; (a+b) - (a+b) = 0)

    3) You left out a negative sign again (look to the left). Be careful!

    4) You might want to check the bracket on the right.

    Good luck!

  3. #13
    New Member
    Join Date
    Jul 2005
    Location
    Vermont
    Posts
    12

    are these correct

    -a(a-b) if a=-2 b=-7
    -2(-2+7)
    -2(5)=-10
    ---------------
    (a-x)(-x) if a=2 x=-5
    2+5(-5)
    7(-5)=-35
    _____________________
    (x-y)-(y-x) if x=-2 y=-4
    (-2+4)+(4-2)
    2+2=4
    Benita

  4. #14
    Elite Member
    Join Date
    Feb 2004
    Location
    Ottawa, Ontario
    Posts
    12,173

    Re: are these correct

    Quote Originally Posted by vermonstervt
    -a(a-b) if a=-2 b=-7
    -2(-2+7)
    -2(5)=-10
    should be 2(-2+7) ; -(-2) = 2
    so answer is +10
    I'm just an imagination of your figment !

  5. #15
    Guest
    Dennis,
    ive seen ALOT of the answers u give out to people. ive analyzed u. and guess wat???

    YOU DON'T GET ALOT OF THE STUFF RIGHT.

    x(x-y) Where
    x=-2
    and
    y=-3

    so the problem to solve would be,

    -2(-2--3)

    2 negatives equal a possitive.

    So that would change the problem into:

    -2(-2+3)

    work within the perenthesis firt. remember pemdas???
    -2+3= POSSITIVE 1



    now,
    -2+1=-1

    OKOKOKOKOKOKOK???????


    ANSWER= -1

  6. #16
    Elite Member stapel's Avatar
    Join Date
    Feb 2004
    Posts
    11,289
    Quote Originally Posted by beautifull_love101
    Dennis, ive seen ALOT of the answers u give out to people. ive analyzed u. and guess wat??? YOU DON'T GET ALOT OF THE STUFF RIGHT.
    Actually Denis (not "Dennis") helps a lot of people, which is more than can be said for your spamming of these forums.

    Eliz.

  7. #17
    Elite Member
    Join Date
    Feb 2004
    Location
    Ottawa, Ontario
    Posts
    12,173
    Quote Originally Posted by beautifull_love101
    So that would change the problem into:
    -2(-2+3)

    you're ok up to here;

    work within the perenthesis firt. remember pemdas???
    -2+3= POSSITIVE 1
    now,
    -2+1=-1

    NO. It's -2 times 1, which equals -2 : answer is -2
    -2(1) means MULTIPLY

    Now go away, you little brat; quit disturbing the site and confusing
    the people who are asking for help...
    I'm just an imagination of your figment !

  8. #18
    Guest
    firt of all im not a brat.
    second you dont talk to me like that.

  9. #19
    Guest
    got it?

  10. #20
    Guest
    WHAT??? you can mess up poeple too. im not the only that makes mistakes.
    you can make thiem too.

Bookmarks

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •